To What Extent Does the Use of "Technological Strategies for Classroom Management" (TSCM) Lessen Third Graders' Disruptive Behaviors in an EFL Class? (2018)
ABSTRACT: This action research study was thought to evaluate the effectiveness of a new approach, Teaching Strategies for Classroom Management (TSCM), designed to diminish disruptive behaviors of third graders in an EFL class at the Institución Educativa Francisco Miranda. Data were collected through four questionnaires to the cooperating teacher and the students, a journal and a behavioral chart. The data analysis revealed that disruptive behaviors diminished after implementing three different strategies: Good Behavior Game (GBG) instructions, technological means, and activities related to the students¿ interests. It was found that some GBG instructions and the use of videos were critical to achieve the main goal because students felt rewarded, motivated and engaged after working cooperatively.